Study of cerebrospinal fluid adenosine deaminase activity for differential diagnosis of tuberculous and non-tuberculous meningitis - Seema Agarwal; Varma, Santosh; Agarwal, Akhil (Asian Journal of Medical Sciences, 2023)
Background: Diagnosing a case of tuberculous meningitis (TBM) has always been challenging. Numerous previous studies have demonstrated that cerebrospinal fluid-Adenosine deaminase (CSF-ADA) estimation is useful in the diagnosis of TBM and can differentiate TBM from other types of meningitis. Aims and Objectives: The current study aims to look for a simple, rapid, cost-effective, and specific test to differentiate tubercular etiology from other causes of meningitis. Materials and Methods: A total of 80 patients admitted to the hospital with signs and symptoms of meningitis were selected and divided into two groups: Group 1 (Cases): 40 patients of TBM, Group 2 (Control): 40 patients of pyogenic and viral meningitis. The CSF ADA was estimated by enzymatic method, CSF Protein by turbidimetric method, and CSF Glucose by Glucose oxidase (GOD) and Peroxidase (POD) method. Results: CSF ADA levels (mean ± SD) in the TBM and non-TBM groups were 10.874+7.72 IU/L and 2.44+1.757 IU/L, respectively (highly significant, P<0.001). With the CSF ADA cut off as >6 IU/L, the sensitivity of the test was 95%, and the specificity of 92.5%. On comparison of the values of CSF ADA in the two groups, the t value is −6.75, and the difference in these two values was found to be highly significant (P<0.01). Conclusion: ADA estimation in CSF is a simple, inexpensive, rapid, and specific method for making a diagnosis of tuberculous etiology in TBM. As a screening test, the determination of ADA activity in CSF can help the physician diagnose TBM early and reduce irreversible brain damage and neurologic sequelae by early administration of anti-tuberculous medications.